A Simple, Rapid, Fluorometric Assay for Dopamine by In Situ Reaction of Boronic Acids and cis-Diol - Xiaoxia Liu; Miaomiao Tian; Wenmei Gao; Jinzhong Zhao (Journal of Analytical Methods in Chemistry)
An efficient, sensitive, and low-cost method has been developed for turn-on fluorescence sensing of dopamine (DA). The method relies on the rapid reaction of DA and 3-Hydroxyphenylboronic acid (3-HPBA) via specific recognition between boronic acids and cis-diol of DA in alkaline solution. The reaction product shows an excitation wavelength of 417 nm and the maximum emission peak at 470 nm. The proposed method allows the determination of DA in the range of 50 nM–25 μM, and the whole detection can be completed within 5 minutes. Furthermore, the presented approach has good selectivity and has been successfully applied to DA sensing in human serum samples, showing great potential in clinical diagnosis.